The Impact of Taxation on the Cost of Living: A Comprehensive Analysis - Siti Aminah Mainal; Fatin Alwani Abu Hanipah; Nur Liyana Zuhaimi; Nur Nuzul Syahira Kamarudin (Information Management and Business Review, 2024)
This study examines the taxation-related factors affecting Malaysia's cost of living. The rising cost of living, a persistent issue in economics and social well-being, is often linked to global challenges faced by emerging nations. Direct tax has been identified as a primary contributor to the financial strain on households, who must manage various essentials beyond food, clothing, and shelter, such as education, cellular services, and transportation. The study analyzes the relationship between seven independent variables—direct tax, unemployment rate, exchange rate, household consumption expenditure, house price index, subsidies, and net trade—and the cost of living in Malaysia, using 30 years of annual data (1992-2022) with EViews for econometric analysis. This study uses descriptive statistical analysis for the description of data, coefficient matrix analysis and regression analysis for determining the impact of dependent and independent variables. The findings show that the cost-of-living pressures are positively correlated with direct tax, housing price index, and net trade. Data was sourced from the National Property Information Centre (NAPIC), the World Bank, and the Economic Planning Unit (EPU). The analysis underscores the significant impact of direct tax on the cost of living. To mitigate this impact, governments could implement fair and progressive tax reforms, provide targeted subsidies, and promote economic growth to boost income levels. Additionally, social programs and efficient government investment can further reduce household financial burdens.